PENGARUH IMPLEMENTASI KURIKULUM MERDEKA TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA NEGERI 1 POLOKARTO SUKOHARJO - Ka’bah, Faza Octavio Abdi Robbil; Hidayah, Nur (STKIP Pesisir Selatan, 2025)
Educational transformation through the Independent Curriculum requires adaptive, competency-based learning approaches that strengthen 21st-century skills, particularly critical thinking. Islamic Religious Education (PAI) plays a strategic role in embedding spiritual, ethical, and social values into students' intellectual development. This study aims to determine the effect of the Independent Curriculum implementation on students’ critical thinking skills in PAI at SMA Negeri 1 Polokarto during the 2024/2025 academic year. Employing a quantitative correlational approach, data were collected via questionnaires and documentation and analyzed using simple linear regression. The findings indicate that both the level of curriculum implementation and students’ critical thinking abilities fall into the high category. A statistically significant effect was found, with the curriculum accounting for 38.1% of the variance in critical thinking skills. These results confirm that the Independent Curriculum serves as a strategic instrument in fostering higher-order thinking within PAI instruction. However, its effectiveness largely depends on teacher readiness, the quality of assessments, and institutional policy support. This study recommends strengthening teacher training and developing more contextual and reflective learning tools.